The Effect of Promotion Through Social Media and Non-Social Media on Patient Visits at Cassandra Skincare Clinic in Singkawang City - Dhea Atiqah Putri; Cecep Darmawan; Kahar Mulyani (CV. Civiliza Publishing, 2026)
This research is against the background of the crucial role of promotion in influencing patient decisions in the health and beauty services sector. Cassandra Skincare Clinic in Singkawang City has used social media, especially Instagram and TikTok as the main means of promotion, with a large follower base. This thesis aims to empirically analyze the influence of promotion in general and the use of social media as a promotional tool specifically on patient visits. The method used was an analytical survey with a cross-sectional study approach of 80 respondents taken through accidental sampling techniques. The results of linear regression analysis showed that promotion (X1) had a very significant influence on patient visits (Y) (Sig. 0.000). Similarly, social media as a promotional tool (X2) also showed a significant influence on visits (Sig. 0.007). The multiple regression model formed was Y = 0.751 + 0.358X1 + 0.132X2, confirming that the two independent variables positively and significantly influenced the patient's interest in visiting. Thus, it is concluded that Cassandra Skincare Clinic needs to prioritize improving the quality of informative and visually appealing social media content and strengthening offline promotional channels to maximize visits.